Exploring Intersectionality in Induk Gajah Season 2: A Literary Perspective on Gender, Culture, and Family Pressure - Agung, I Gusti Ayu Mahatma; Saragih, Tesalonika; Batubara, Lexandra Kathlyn (Journal of Language and Literature Studies, 2025)
This study explores the role of intersectionality, as theorized by Crenshaw, in shaping gendered experiences within patriarchal cultures as represented in Induk Gajah Season 2. It focuses on how cultural norms, family expectations, and societal pressures intersect to impact women’s autonomy and well-being. The research drew on dialogues from selected scripted scenes in the series and employed qualitative, thematic analysis to examine how reproductive and familial expectations create specific pressures on women. The findings reveal that within the depicted patriarchal system, women’s choices are often marginalized in favor of family honor and cultural conformity, leading to the normalization of gender-based inequality. This pattern reflects a broader cultural issue where reproductive roles define women’s worth, limiting their freedom in decision-making and reinforcing systemic discrimination. The study concludes that intersectionality provides a crucial lens for understanding how overlapping social identities and cultural expectations create unique challenges for women. By applying an intersectional lens to a media text, the study contributes to gender and media studies by illustrating how traditional values are represented, negotiated, and potentially challenged in popular cultural narratives. It also highlights the need for further research into how traditional values and family structures shape women’s experiences, particularly in contexts where cultural pride and social reputation are placed above individual rights.